Inibidores da enzima de conversão da endotelina e sua aplicação na patologia cardiovascular. - Cerdeira, Ana (2008)
Endothelin, a potent vasoconstrictor first described in 1988 by Yanagisawa, is an important regulator of cardiovascular function. Hyperactivation of the endothelin system has been implicated in the pathogenesis of various cardiovascular disorders including myocardial infarction, restenosis, hypertension, heart failure and Chagas cardiopathy. Various attempts have been made to suppress this axis. Although promising, the results of clinical trials on endothelin receptor antagonists have been disappointing. There is growing interest in blockade of endothelin formation. Several selective and non-selective endothelin-converting enzyme (ECE) inhibitors have been developed, the latter with the possibility of simultaneously blocking angiotensin-converting enzyme and neutral endopeptidase, combining inhibition more than one axis. This article reviews the different ECE inhibitors, with particular emphasis on their potential clinical application in cardiovascular diseases